PEMAKNAAN WACANA KRITIK KEKUASAAN DALAM LAGU PUNK “GELAP GEMPITA” KARYA SUKATANI OLEH DEMONSTRAN INDONESIA GELAP - Khizbulloh Huda; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Research on the punk subculture in Indonesia shows that anarchism is not merely an aesthetic but an ideological foundation of daily communal life. However, studies remain focused on internal subcultural actors, while mainstream reception is scarcely addressed. The police ban on Sukatani's work in February 2025, intersecting with the Indonesia Gelap demonstrations, marked a moment when anarchist texts circulated as protest anthems in public, opening the study of mainstream reception. Drawing on John Fiske's popular culture model through in-depth interviews with five demonstrators, this study finds that platform mediation decontextualized “Gelap Gempita,” while state repression triggered repoliticization. Despite diverse ideological positions, all participants formed a convergent relational pattern positioning dominant power against subordinate resistance: four negotiated anarchism into democratic critique, one embraced it more fully. The producerly text enables polysemy, yet the limited discursive legacy of the Left post-New Order constrains articulation within the logic of formal institutions.